The use of a geographic information system to increase outdoor tourism - Scalabrini, E.C.B. (2022)
Purpose: Outdoor tourism is a growing segment that still requires data for planning and management. Aimed to present the potential of the Geographic Information System (GIS) to improve outdoor tourism in the North of Portugal. To achieve this purpose, a case study was conducted on developing a Web-GIS in Northern Portugal. Methodology: Four steps were followed to develop the GIS tool with information about outdoor tourism in the North of Portugal. In the first step, municipalities in the North of Portugal sent information about outdoor activities. In the second step, the data were georeferenced and associated. In the last step, a Web-GIS was developed. Findings: The development of tools is an important source of support for tourism. This study identified that a tool such as the GIS could support a destination's decision-making and promotional processes, besides providing detailed information to the tourist and facilitating travel planning. Practical implications: GIS provides effective planning of outdoor tourism, once this tool allows an effective search of the tourist offer and, from the tourist's perspective, relevant suggestions of visits according to their location are presented, facilitating their experience in the region. Originality: Several studies relate to GIS and tourism, but there is still a gap in specific studies on outdoor activities. So, this study presents the importance of GIS to improve outdoor tourism in the North region of Portugal. Understanding this importance is essential in planning and managing tourism, helping further policymaking and marketing strategies.